ISO 9001:2015 : in plain English - Cochran, Craig (Paton Professional, 2015)
"ISO 9001 hasn't changed much in the last 15 years... until now! ISO 9001:2015 is a MAJOR revision. A LOT has changed. Requirements have been added and removed. Content has shifted to different sections and clauses. ISO 9001:2015 is built upon a completely different structure with the adoption of Annex SL. This may seem like a lot to take in, and it is. Fortunately, bestselling author Craig Cochran has translated ISO 9001:2015 into plain English that anyone can understand. Just as he did with the bestselling ISO 9001 in Plain English Cochran has written a comprehensive yet easily understandable guide to ISO 9001:2015. ISO 9001:2015 in Plain English was written so that anyone at any level of the organization can get to the heart of the standard's requirements and how they apply to the organization quickly and simply. Plus, Cochran shows what has changed between the 2008 and 2015 version. This straightforward book is ideal for people who are new to ISO 9001:2015, experienced ISO coordinators who want to get more out of an established system as they transition to the new standard, and for employees who just need a basic understanding of what ISO 9001:2015 is and how it applies to them. Cochran explains each of ISO 9001:2015's sections and clauses using real-world examples and frequently asked questions."